Effect of Guatamala grass (Tripsacum laxum) mulch applications on soil moisture conservation and soil fertility status - Asten, Piet J.A. van; Twagirayezu, A.; Gaidashova, S.V. (2007)
Mulch applications generally have a large beneficial effect on the productivity of important perennial cash crops in the East African Highlands such as bananas (Musa spp.) and coffee (Coffea spp.), due to the conservation of soil moisture and the improvement of soil fertility. However, the availability of mulch to farmers is often limiting and validated recommendations on optimal mulch thicknesses in the region are absent. Informal interviews with researchers and farmers revealed that a 10 cm mulch thickness is often considered optimal. We monitored soil moisture content and soil fertility under 0, 5, 10 and 20 cm mulch thickness using Guatamala grass (Tripsacum laxum) in shaded and non-shaded plots in order to mimic the effects of mulch applications in newly planted fields and fields with an established canopy. The study took place in uncultivated plots of 2x2m between July and November 2005 at the ISAR research station in Rubona, Rwanda. The results showed that in a 1 m soil profile, application of 5, 10 and 20 cm of mulch significantly (p<0.001) increased average soil moisture content by 63, 88 and 72 %, respectively. After 4 months, application of 20cm mulch had significantly (p<0.05) increased available P from 14 to 21 ppm, mineral N from 3.1 to 5.4 %, and K from 2.1 to 2.7 cmolc 100 g-1 in the topsoil (0-30 cm). Smaller mulch applications of 5 and 10 cm showed proportional intermediate increases in soil fertility. The thickness of the mulch layers reduced by 44% over the four months period. This trial shows that mulch applications of half the perceived optimal rate already have a large impact in terms of moisture conservation and additional increases in mulch thickness have relatively little additional impact. However, increases in soil fertility due to mulch are strongly correlated with the mulch quantities applied.